Globalization and the Welfare State. - Mishra, Ramesh (E. Elgar, 1999)
"Does globalization mean a race to the bottom in social standards and the inevitable decay of the welfare state? Ramesh Mishra - a leading authority on social policy - examines the implications of globalization in respect of social policy and social standards in advanced industrial countries." "Globalization and the Welfare State is highly accessible and will be welcomed by students and scholars of social policy, social work, political science and sociology as well as by policymakers in international organizations and government."--Jacket.
1. The logic of globalization: the changing context of the welfare state -- 2. Employment, labour market and income: growing insecurity and inequality -- 3. Social policy in retreat or the hollowing out of the welfare state -- 4. Social policy and democracy: do politics still matter? -- 5. Globalization in comparative perspective: Sweden, Germany and Japan -- 6. The logic of globalization revisited -- 7. Towards a global social policy.
Keywords: Welfare state; Social policy; Public Policy